class (Applicative m) => Monad m where -- m :: * -> *
return :: a -> m a -- return
(>>=) :: m a -> (a -> m b) -> m b -- bind
data Maybe a = Nothing | Just a
instance Monad Maybe where
return :: a -> Maybe a
return = Just
(>>=) :: Maybe a -> (a -> Maybe b) -> Maybe b
Nothing >>= _ = Nothing
Just a >>= f = f a
ghci> Just 5 >>= (\x -> Just $ x + 3)
Just 8
ghci> Just 5 >>= (\x -> return $ x + 3)
Just 8
maybePair :: Maybe a -> Maybe b -> Maybe (a, b) -- naive implementation
maybePair Nothing _ = Nothing
maybePair _ Nothing = Nothing
maybePair (Just a) (Just b) = Just (a, b)
ghci> Nothing >>= (\x -> return $ x + 3)
Nothing
ghci> Just 3 >>= \x -> Just 4 >>= \y -> Just (x + y)
Just 7
maybePair :: Maybe a -> Maybe b -> Maybe (a, b) -- monadic implementation
maybePair ma mb = ma >>= \a -> mb >>= \b -> Just (a, b)
monadPair :: Monad m => m a -> m b -> m (a, b) -- polymorphic implementation
monadPair ma mb = ma >>= \a -> mb >>= \b -> return (a, b)
stripUsername :: String -> Maybe String
stripUsername "" = Nothing
stripUsername name@(n:ns) = case isSpace n || isPunctuation n of
True -> stripUsername ns
False -> Just name
validateLength :: Int -> String -> Maybe String
validateLength maxLen s = if length s > maxLen
then Nothing
else Just s
newtype Username = Username String deriving (Eq, Show)
mkUser :: String -> Maybe Username -- FP programming pattern: smart constructor
mkUser name = ???
mkUser :: String -> Maybe Username -- FP programming pattern: smart constructor
mkUser name = case stripUsername name of
Nothing -> Nothing
Just name' -> case validateLength 15 name' of
Nothing -> Nothing
Just name'' -> Just $ Username name''
mkUser :: String -> Maybe Username -- FP programming pattern: smart constructor
mkUser name = stripUsername name >>= validateLength 15 >>= return . Username
mkUser :: String -> Maybe Username -- FP programming pattern: smart constructor
mkUser name = stripUsername name >>= \name' ->
case validateLength 15 name' of
Nothing -> Nothing
Just name'' -> Just $ Username name''
mkUser :: String -> Maybe Username -- FP programming pattern: smart constructor
mkUser name = stripUsername name >>= \name' ->
validateLength 15 name' >>= \name'' ->
Just $ Username name''
newtype Identity a = Identity { runIdentity :: a }
instance Monad Identity where
return = Identity
i >>= f = ...
data Either e a = Left e | Right a
instance Monad ...
ghci> :kind Either
Either :: * -> * -> *
instance Monad (Either a) where ... -- Either a :: * -> *
ghci> :kind Either String
Either String :: * -> *
ghci> :kind Either Int
Either Int :: * -> *
instance Monad (Either e) where ... -- Either a :: * -> *
return :: a -> Either e a
instance Monad (Either e) where ... -- Either a :: * -> *
return :: a -> Either e a
return = Right
instance Monad (Either e) where ... -- Either a :: * -> *
return :: a -> Either e a
return = Right
(>>=) :: Either e a -> (a -> Either e b) -> Either e b
instance Monad (Either e) where ... -- Either a :: * -> *
return :: a -> Either e a
return = Right
(>>=) :: Either e a -> (a -> Either e b) -> Either e b
Left e >>= f = ...
Right a >>= f = ...
instance Monad (Either e) where ... -- Either a :: * -> *
return :: a -> Either e a
return = Right
(>>=) :: Either e a -> (a -> Either e b) -> Either e b
Left e >>= _ = Left e
Right a >>= f = f a
data ValidationError = InvalidStrip | TooBigLength
stripUsername :: String -> Either ValidationError String
stripUsername "" = Left InvalidStrip
stripUsername name@(n:ns) = case isSpace n || isPunctuation n of
True -> stripUsername ns
False -> Right name
validateLength :: Int -> String -> Either ValidationError String
validateLength maxLen s = if length s > maxLen
then Left TooBigLength
else Right s
mkUser :: String -> Either ValidationError Username
mkUser name = stripUsername name >>= validateLength 15 >>= return . Username
ghci> mkUser " "
Left InvalidStrip
ghci> mkUser " ... I Am The Greatest Hero Of All Times ... "
Left TooBigLength
ghci> mkUser "JustSenia..."
Right ( Username "JustSenia..." )
ghci> Right True >>= \_ -> Right "foo"
Right "foo" :: Either a [Char]
ghci> Right True >>= \_ -> Left "foo"
Left "foo" :: Either [Char] b
ghci> Left True >>= \_ -> Right "foo"
Left True :: Either Bool [Char]
ghci> Left True >>= \_ -> Left "foo"
• Couldn't match type ‘[Char]’ with ‘Bool’
Expected type: Either Bool b
Actual type: Either [Char] b
• In the expression: Left "foo"
In the second argument of ‘(>>=)’, namely ‘\ _ -> Left "foo"’
In the expression: Left True >>= \ _ -> Left "foo"
You can't mix Left's of different types inside one monadic computation (sequence of >>=). Make sure you understand next code block:
(.) :: (b -> c) -> (a -> b) -> a -> c
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c
m >>= (f >=> g) ≡ m >>= f >>= g
m >>= (f <=< g) ≡ m >>= g >>= f
(f >=> g) >=> h ≡ f >=> (g >=> h) -- associativity
safeTail :: [a] -> Maybe [a]
safeInit :: [a] -> Maybe [a]
safeStrip :: [a] -> Maybe [a]
safeStrip = safeTail >=> safeInit
(>=>) :: Monad m => (a -> m b) -> (b -> m c) -> a -> m c
stripUsername :: String -> Maybe String
validateLength :: Int -> String -> Maybe String
mkUser :: String -> Maybe Username
mkUser name = stripUsername name >>= validateLength 15 >>= Just . Username
mkUser = stripUsername >=> validateLength 15 >=> Just . Username
instance Monad [] where
return :: a -> [a]
return x = [x] -- using bender-operator: return = (:[])
(>>=) :: [a] -> (a -> [b]) -> [b]
l >>= f = concat (map f l) -- or using concatMap
ghci> [10, 5, 7] >>= replicate 3
[10, 10, 10, 5, 5, 5, 7, 7, 7]
surround :: a -> a -> [a] -> [a]
surround '(' ')' "abacaba" = "(a)(b)(a)(c)(a)(b)(a)"
ghci> [1..5] >>= \x -> replicate x x
[1,2,2,3,3,3,4,4,4,4,5,5,5,5,5]
ghci> let step x = [x - 1, x + 1]
ghci> [0] >>= step
[-1,1]
ghci> [0] >>= step >>= step
[-2,0,0,2]
ghci> [0] >>= step >>= step >>= step
[-3,-1,-1,1,-1,1,1,3]
ghci> [0] >>= step >>= step >>= step >>= step
[-4,-2,-2,0,-2,0,0,2,-2,0,0,2,0,2,2,4]
(>>) :: Monad m => m a -> m b -> m b -- then
m >> k = m >>= \_ -> k
ghci> Just 3 >> Just 5
Just 5
ghci> Nothing >> Just 5
Nothing
_ >> k = k
ghci> [True,False] >> [1,2,3]
[1,2,3,1,2,3]
-- 'guard' is a polymorphic function but for lists looks like this:
guard :: Bool -> [()]
guard True = [()]
guard False = []
ghci> [True,False,True] >> [1,2]
[1,2,1,2,1,2]
ghci> [True,False,True] >>= \b -> guard b >> [1,2]
[1,2,1,2]
join :: Monad m => m (m a) -> m a
ghci> join [[3, 4], [7, 10]]
[3, 4, 7, 10]
ghci> join Just (Just 3)
Just 3
extract :: Monad m => m a -> a -- ??
ghci> join $ Just [1,2,3]
• Couldn't match type ‘[]’ with ‘Maybe’
Expected type: Maybe (Maybe a)
Actual type: Maybe [a]
• In the second argument of ‘($)’, namely ‘Just [1, 2, 3]’
In the expression: join $ Just [1, 2, 3]
In an equation for ‘it’: it = join $ Just [1, 2, 3]
ghci> join (,) 1 -- niiice
(1,1)
ghci> join replicate 3
[3,3,3]
data Repeat a = Empty | Single a | Repeat a
instance Monad Repeat where
return :: a -> Repeat a
return = Single
(>>=) :: Repeat a -> (a -> Repeat b) -> Repeat b
Empty >>= _ = Empty
Single a >>= f = f a
Repeat a >>= f = f a >>= f
-- what's the problem with Repeat?
Sometimes simple types can be monads. But in not obvious way.
data Foo a = Bar a | Baz a a
liftM :: Monad m => (a -> b) -> m a -> m b
liftM2 :: Monad m => (a -> b -> c) -> m a -> m b -> m c
ghci> liftM2 (+) (Just 1) (Just 2)
Just 3
ghci> monadPair (Just 3) (Just 5)
Just (3,5)
ghci> monadPair (Just 3) Nothing
Nothing
ghci> monadPair [1..3] [5,10]
[(1,5), (1,10), (2,5), (2,10), (3,5), (3,10)]
ghci> liftM (+1) (Just 3)
Just 4
ghci> liftM (+1) Nothing
Nothing
ghci> let monadPair = liftM2 (,)
monadPair :: Monad m => m a -> m b -> m (a, b)
(||^) :: Monad m => m Bool -> m Bool -> m Bool -- lazy monadic ||
(&&^) :: Monad m => m Bool -> m Bool -> m Bool -- lazy monadic &&
ghci> Just False ||^ Just True
Just True
ghci> Just False &&^ Just True
Just False
ghci> Just False &&^ Nothing
Just False
ghci> Just True &&^ Nothing
Nothing
ghci> Nothing &&^ Just True
Nothing
1. return a >>= f ≡ f a -- left identity
2. m >>= return ≡ m -- right identity
3. (m >>= f) >>= g ≡ m >>= (\x -> f x >>= g) -- associativity
To prove one thing equals to another you can use so-called Equational reasoning technique — step-by-step transformation
Lets prove 'foldr (+) 0 [1,2,3] ≡ 6'
foldr :: (a -> b -> b) -> b -> [a] -> b
foldr _ z [] = z -- (1) case
foldr f z (x:xs) = x `f` foldr f z xs -- (2) case
foldr (+) 0 [1,2,3] ≡ 1 + foldr (+) 0 [2,3] -- using (2)
≡ 1 + (2 + foldr (+) 0 [3]) -- using (2)
≡ 1 + (2 + (3 + foldr (+) 0 [])) -- using (2)
≡ 1 + (2 + (3 + 0)) -- using (1)
≡ 1 + (2 + 3) -- definition of (+)
≡ 1 + 5 -- definition of (+)
≡ 6 -- definition of (+)
So, basically, just sequence of β-redunctions
instance Monad Maybe where
return = Just -- (1): return
Nothing >>= _ = Nothing -- (2): bind-Nothing
Just a >>= f = f a -- (3): bind-Just
This can be used to prove laws.
Let's prove Monad laws for Maybe
LAW: return a >>= f ≡ f a
LAW: m >>= return ≡ m
return a >>= f ≡ Just a >>= f -- (1): return
≡ f a -- (3): bind-Just
Nothing >>= return
≡ Nothing -- (2): bind-Nothing
Just a >>= return
≡ return a -- (3): bind-Just
≡ Just a -- (1): return
instance Monad Maybe where
return = Just -- (1): return
Nothing >>= _ = Nothing -- (2): bind-Nothing
Just a >>= f = f a -- (3): bind-Just
LAW: (m >>= f) >>= g ≡ m >>= (\x -> f x >>= g)
1. (Nothing >>= f) >>= g
≡ Nothing >>= g -- (2): bind-Nothing
≡ Nothing -- (2): bind-Nothing
1. (Just a >>= f) >>= g
≡ f a >>= g -- (3): bind-Just
2. Nothing >>= (\x -> f x >>= g)
≡ Nothing -- (2): bind-Nothing
2. Just a >>= (\x -> f x >>= g)
≡ (\x -> f x >>= g) a -- (3): bind-Just
≡ f a >>= g -- function application
m ≡ Nothing
m ≡ Just a
powerset :: [a] -> [[a]] -- all subsets of given list
They will tell you that list monad is about non deterministic evaluation. What does it mean?..
ghci> powerset [1,2,3]
[ [], [ 1 ], [ 2 ], [ 1, 2 ], [ 3 ], [ 1, 3 ], [ 2, 3 ], [ 1, 2, 3 ] ]
-- How to choose nondetermistically subset of list?
subset [] = []
subset (x : xs) = subset xs OR x : subset xs
powerset :: [a] -> [[a]]
powerset [] = [[]]
powerset (x:xs) = powerset xs >>= \set -> [set, x:set]
Replace OR with AND to get all subsets
data CoinType = Fair | Biased deriving (Show)
data Coin = Head | Tail deriving (Show, Eq)
You have two coins, labeled Biased and Fair. The Biased coin has two heads, and the Fair coin has one head and one tail. Pick one of these coins at random, toss it and observe the result. If the result is a head, what is the probability that you picked the Biased coin?
toss :: CoinType -> [Coin]
toss Fair = [Head, Tail]
toss Biased = [Head, Head]
pick :: [CoinType]
pick = [Fair, Biased]
experiment :: [CoinType]
experiment =
pick >>= \coin -> -- Pick a coin at random
toss coin >>= \result -> -- Toss it, to get a result
guard (result == Head) >> -- We only care about results that come up Heads
return coin -- Return which coin was used in this case
ghci> experiment
[Biased, Biased, Fair] -- 2/3 chance for Biased and 1/3 chance for Fair
experiment :: [CoinType]
experiment = [coin | coin <- pick, result <- toss coin, result == Head]